Magic and a new pedagogical relationship with early childhood - Suárez Vaca, María Teresa (Universidad Pedagógica y Tecnológica de Colombia, 2010)
Based on the reflection about the practices of the author and in the light of the study of literature in relation to magic and pedagogical relationship, as well as several research projects, including her own Master’s Degree project in Education, this article analytically presents and develops four ideas: magic at the limits of modern science, as a cultural construction that has challenged reality and imagination, early childhood, as a dynamic process of the human being, linked to curiosity, exploratory power, audacity, possibilities of being and becoming, the early childhood educator as driving force of cognitive processes and learning environments, and finally, a new way to understand pedagogical relationship with preschoolers that arises from the critical examination of the previous information.